A layered approach to model interconnected infrastructure and its significance for asset management - Bhamidipati, Srirama; Lei, Telli van der; Herder, Paulien (European Journal of Transport and Infrastructure Research, 2016)
Physical infrastructures facilitate much of societal and economic wellbeing of countries, regions and urban areas. In our increasingly urbanizing world, infrastructures in urban areas are densely located and interconnected. The effects of this interconnectedness are being studied increasingly, particularly in light of climate change effects. In this paper, we develop an agent-based simulation model that allows us to study interconnected infrastructure. We present a layered approach that is analogous to GIS overlay approaches, which allows us to integrate representations of different infrastructures. We explore how this approach can help asset managers to gain insights in interconnected infrastructure by estimating their total damage and repair requirements during a flood event. The results show a difference in these estimates, when compared to non-integrated models, highlighting the need for asset managers to consider interconnectedness in infrastructure.